Surface tailored PS/TiO2 composite nanofiber membrane for copper removal from water - Wanjale, Santosh; Birajdar, Mallinath S.; Jog, Jyoti Prakash; Neppalli, Ramesh; Causin, Valerio; Karger-Kocsis, Jozsef; Lee, Jonghwi; Panzade, Prasad (Journal of Colloid and Interface Science, 2016)
Polystyrene (PS)/TiO2 composite nanofiber membranes have been fabricated by electrospinning process for Cu2+ ions removal from water. The surface properties of the polystyrene nanofibers were modulated by introducing TiO2 nanoparticles. The contact angle of the PS nanofiber membrane was found to be decreased with increasing concentration of TiO2, depicted enhanced hydrophilicity. These membranes were highly effective in adsorbing Cu2+ ions from water. The adsorption capacity of these membranes was found to be 522 mg/g, which is significantly higher than the results reported by other researchers. This was attributed to enhanced hydrophilicity of the PS/TiO2 composite nanofiber membranes and effective adsorption property of TiO2 nanoparticles. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: electrospinning; Metal ion adsorption; Nanofiber; TiO2; Water treatment/purification